Phonocadencies in Epic Genres: Toyuk and Olonkho - Alexeev, Ivan Egorovich; Sorova, Irina Nikolaevna (Journal of History Culture and Art Research, 2018)
This article deals with structurally-phonomorphological and typical acoustic phonocadency in Yakut toyuk and olonkho, performed by outstanding artists of folklore and professional storytelling S.A. Zverev and G.G. Kolesov. Experimentally-linguistic analysis was carried out with computer program “Speech Analyzer”. Phonocadency as a structural part of epic chant has been specific acoustic complex of components of intonation (quantitativeness, tonality and dynamic indicators). It has three kinds of realization in toyuk, olonkho and algys: initial, medial and final in melodic axis. Most often it functions as a phonoproclitic-enclitic component with various vocal modulations in a form of vibrato and kylyhaakh (throaty signs of chant). Initial and medial phonocadencies are less quantitative than final ones. In general, these acoustic indicators serve as more plangent exclamation in epic chants. Factual and relative phonetic characteristics of phonoproclitics, phonomedial and phonoenclitics of S.A. Zverev’s toyuks have typological commonality with epic pieces of art (olonkho, algys) and are etiquette and universal signs, which symbolize the core of Yakut musical culture of oral traditions. Initial and final phonocadencies of Nyurgun Bootur’s songs from Oyunsky’s olonkho are expressed by generating physiological vibrato and various vocal modulations. They demonstrate strength and frequency of vocal timbre and also they reveal epic image of a hero.